(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2020)
Due to the existing trend of English as a global language, coupled with the emerging trend of regionalisation, individual national culture and identity have attenuated. Concerns regarding the increasing influx of foreign influence through a multitude of channels have been exacerbated by the augmented popularity of social media that permeates most aspects of people’s lives. As a consequence, particularly in the Thai context, Thai culture and identity is vulnerable. This presentation represents an attempt to avoid such imminent subjugation and simultaneously preserve the national identity of Thai learners. Specifically, this study highlights local cultural features pertaining to southern Thailand, manifested through a set of English lessons constructed and subsequently implemented to elementary students in southern Thailand for ten weeks. Based on the tests devised to measure the students’ southern Thailand knowledge and associated English vocabulary, the southern Thainess-based English lessons exert a significantly positive impact on English language learning and cultural awareness. As demonstrated, the local culture-based English lessons can be manipulated as a viable and legitimate channel to address learners’ local culture. By extension, English education can be deemed as an ideal and promising avenue to integrate other academic disciplines to empower learners to be equipped for the demands of the 21st century.